Effect of fibre-matrix interfacial strength on the explosive blast resistance of carbon fibre laminates. (18th January 2017) - Gargano, A.; Pingkarawat, K.; Pickerd, V.L.; Ibrahim, M.E.; Mouritz, A.P.
Abstract: The influence of the fibre-polymer matrix interfacial bond strength on the explosive blast response of carbon fibre laminates is experimentally investigated. Air blast tests were performed on laminate target panels containing woven carbon fabric treated with a fibre-sizing agent that promoted either weak or strong bonding with the polymer matrix. The laminates were subjected to increasing shock wave impulse loads by increasing the mass or reducing the stand-off distance of the plastic explosive charge. High-speed digital image correlation photography (DIC) during explosive blast testing revealed the dynamic deformation responses and surface strains of the laminate targets were not influenced significantly by the type of fibre-sizing agent, except at high shock wave impulse levels. However, non-destructive testing using ultrasonics and X-ray computed tomography revealed that the initiation and growth of blast-induced damage (e.g. delamination cracks, matrix cracks, fibre fracture) was dependent to the interfacial bond strength. Damage occurred at a high shock impulse level in the laminate with strong fibre-matrix interfacial bonding, and this is attributed to higher flexural and interlaminar fracture toughness properties compared to the composite with weak interfacial bonding. The post-blast mechanical properties were also higher for the laminate with strong interfacial bonding. This study reveals that the fibre-sizing agent has a substantial influence on the explosive blast resistance and post-blast properties of laminates, and it is essential that an agent having high chemical compatibility with the polymer matrix is used to promote strong bonding.